A new broadband circularly polarized square‐slot antenna with low axial ratios. Issue 1 (24th September 2018) - Wang, Lei; Fang, Wenxiao; En, Yunfei; Huang, Yun; Shao, Weiheng; Yao, Bin
Abstract: A new broadband circularly polarized (CP) square‐slot antenna with low axial ratios is proposed in this article. The antenna is comprised of an L‐shaped microstrip line with tapered section and a square‐slot ground plane with some stubs and slots, which are utilized as perturbations for the desirable antenna performance. By loading stubs and slots in the square‐slot ground plane, the 2‐dB axial ratio bandwidth (ARBW) and 10‐dB return loss bandwidth for the presented antenna can be markedly improved. The measured results show that its 2‐dB ARBW is 4.2 GHz (54.2% from 5.65 GHz to 9.85 GHz) and its 10‐dB return loss bandwidth is about 8.9 GHz (92.7% from 5.15 GHz to 14.05 GHz). The proposed antenna features compact structure and broad 2‐AR bandwidth which could completely cover the WLAN (5.725‐5.85 GHz) band. Therefore, the proposed antenna is suitable for circular polarization applications in C band.